Whole-school sustainability at the core of quality education: Wished for by principals but requiring collective and structural action - Jorrit Holst; Antje Brock; Julius Grund; Ann-Kathrin Schlieszus; Mandy Singer-Brodowski (Journal of Cleaner Production, 2025)

Emotions and transformative learning for sustainability: a systematic review - Julius Grund; Mandy Singer-Brodowski; Alexander Georg Büssing (Sustainability Science, 2024)
As multiple global sustainability crises are getting more severe and existential, a better understanding of how people undergo deep personal transformations related to sustainability is needed. In the educational debate on sustainability learning, transformative learning theories are widely used. To analyze specific phases of transformative learning, we derived five meta-phases from the literature (novel experience, reflection, social exchange, shift of action, shift of meaning). Although human emotions often arise during the confrontation with sustainability issues and are central to moral action, no substantial, theorized understanding of the role of emotions within sustainability-related transformative learning exists to date. We conducted a systematic review (following the PRISMA guidelines) and screened 355 publications to close this research gap. After applying the exclusion criteria, the in-depth analysis of 20 studies showed that sound theoretical references to theories of emotion and transformative learning are rare. The review shows clearly that diverse emotions permeate sustainability-related transformative learning processes. Among these are both negative emotions to novel learning experiences concerning sustainability (e.g., sadness, shame, disgust, guilt) as well as positive emotions in the context of social exchange (e.g., awe, gratitude, fun) and associated with newly formed actions (e.g., fulfillment, pride). Accordingly, to enable emotionally positive learning experiences, relationship and action orientation are particularly important within sustainability learning. The analyzed studies call for an educational practice where emotions can be experienced, expressed, and understood in a safe atmosphere. Future research in this area should use more stable theoretical foundations for emotions and transformative learning theory and apply methods that can capture deeper levels of subjective experience.

The potential of transformative learning for sustainability transitions: moving beyond formal learning environments - Mandy Singer-Brodowski (Environment, Development and Sustainability, 2023)
Transformative learning has become one of the most prominent learning theory in regard to sustainable development. It holds enormous potential for explaining and accompanying learning processes related to processes of transformation for sustainability, especially due to its emphasis on changing meaning perspectives in discussions with others in spaces free of coercion. In addition, it inspires learners and educators to pay particular attention to emotional challenges when they engage in critical thinking. This theoretical paper explores the potential of transformative learning theory by examining informal learning environments where people do not explicitly intend to learn but learning happens en passant or incidentally. It shows the ability of transformative learning theory to explain what can happen on the level of individual learning, organizational learning, learning in multi-professional networks, and learning in transdisciplinary or transformative research cooperation processes. Based on this analysis, recommendations can be derived to stimulate, enable, and accompany transformative learning processes for sustainability.